3(x-1)+60=8(x+4)

Simple and best practice solution for 3(x-1)+60=8(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)+60=8(x+4) equation:


Simplifying
3(x + -1) + 60 = 8(x + 4)

Reorder the terms:
3(-1 + x) + 60 = 8(x + 4)
(-1 * 3 + x * 3) + 60 = 8(x + 4)
(-3 + 3x) + 60 = 8(x + 4)

Reorder the terms:
-3 + 60 + 3x = 8(x + 4)

Combine like terms: -3 + 60 = 57
57 + 3x = 8(x + 4)

Reorder the terms:
57 + 3x = 8(4 + x)
57 + 3x = (4 * 8 + x * 8)
57 + 3x = (32 + 8x)

Solving
57 + 3x = 32 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
57 + 3x + -8x = 32 + 8x + -8x

Combine like terms: 3x + -8x = -5x
57 + -5x = 32 + 8x + -8x

Combine like terms: 8x + -8x = 0
57 + -5x = 32 + 0
57 + -5x = 32

Add '-57' to each side of the equation.
57 + -57 + -5x = 32 + -57

Combine like terms: 57 + -57 = 0
0 + -5x = 32 + -57
-5x = 32 + -57

Combine like terms: 32 + -57 = -25
-5x = -25

Divide each side by '-5'.
x = 5

Simplifying
x = 5

See similar equations:

| g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 | | -8=x/4+3 | | 3y=5x-y | | 5x+10=-48-7x | | 5(-3x-7)=-4(4x+9) | | 6(x-1)-5=4x+2(-3+x) | | 55-(2c+3)=4c(c+6)+c | | 7y+9=30 |

Equations solver categories